What is early modern history? - Wiesner, Merry E. 1952- (polity, 2021)
1. Economic and social history -- 2. Religious, intellectual, and cultural history -- 3. Women's, gender, and sexuality studies -- 4. The Atlantic world -- 5. The global early modern -- 6. Popular and public history -- Afterword: The future of early modern history/studies?
Includes bibliographical references and index
Keywords: Geschichte 1450-1800; Geschichtswissenschaft; Geschichte; Periodisierung; Neuzeit; History, Modern / 16th century / Historiography; History, Modern / 17th century / Historiography; History, Modern / 18th century / Historiography; History, Modern / 16th century; History, Modern / 17th century; History, Modern / 18th century